Temporihygrophilous Quercus broteroi forests in southern Portugal: analysis and conservation - Vila-Viçosa, C. (2012)
This article deals with a phytosociological survey of marcescent Portuguese oak (Quercus broteroi) forests in southern Portugal, and presents the results of an analysis of 56 releve´s, combining Braun–Blanquet’s methodology with hierarchical cluster analysis (Ward’s Hierarchical Clustering, based on Bray–Curtis distance). From these results, a new temporihygrophilous Portuguese oak forest association is described. Largely thermomediterranean, upper dry to subhumid, Ulici welwitschiani–Quercetum broteroi occurs on limestone soils within the Coastal Lusitan-Andalusian Province. Its high conservation value – mainly due to its rarity and floristic structure – supports this forest’s integration in Habitat 9240 (Annex B-I from Council Directive 92/43/EEC) in order to ensure its preservation. Based on the results, new biogeographic borders for the Ribatagan-Sadensean Sector are proposed